Ocorrência, susceptibilidade a antifúngicos e fatores de virulência de leveduras oportunistas isoladas de praias dos estados do Rio de Janeiro e Paraná - Natália Oliveira Pereira Maciel (2014)
The main objective of this work was to determine the occurrence of Candida albicans and other opportunistic yeasts in sand and water samples from beaches in Brazil and try to correlate these microorganisms with the conventional indicators of fecal pollution. Pathogenic potential of these yeasts was also assessed by the research of virulence factors and the susceptibility to usual antifungal drugs. A total of 72 water samples and 144 sand samples were collected during the year 2010. Sand suspensions and water samples were filtered through sterile membranes and the filters were placed onto three different culture media. To determine the total yeast counts, it was used the YM agar plates that were incubated at 25ºC. For the differential isolation of Candida species, it was used the CHROMagar-Candida plates that were incubated at 37ºC. The isolation of possible C. albicans strains was performed on mCA agar at 37ºC. Yeasts were identified by sequencing of the D1/D2 variable domains of the large-subunit of the gene of the rRNA. Yeast isolates belonging to opportunistic species were evaluated regarding their susceptibility to fluconazole, itraconazole and amphotericin B. The presence of virulence factors such proteinase production, adhesion to buccal epithelial cells, morphogenesis, and the in vitro and in vivo biofilm formation on catheter pieces were also investigated. Finally, strains were selected for carrying out virulence tests using Balb/c mice as model. Escherichia coli and total coliforms were enumerated by using the defined substrate technology (Colilert). Yeast counts ranged from 0 to 408CFU/g for sand and from 0 to 172CFU/100mL for water. There were no significant correlations between yeast and indicator bacteria densities in the collected samples. Among the 96 different yeast species isolated in CHROMagar-Candida, C. parapsilosis was the most prevalent, followed by Rhodotorula mucilaginosa and Meyerozyma guilliermondii. Only three of 74 yeast isolates in mCA agar were identified as C. albicans. Sixty one percent of the 144 evaluated yeasts presented resistance or dose-dependent sensibility to at least one tested drug. Regarding the proteinase production, 41% of the 144 evaluated strains showed halo formation on medium containing bovine serum albumin, and thus were considered positive. Species that presented the highest rates of adhesion to buccal epithelial cells (BEC) were C. albicans with an average of 146 yeasts every 50 BECs, and Kodamaea ohmeri with 286 yeasts every 50 BECs. All C. albicans strains that were tested were able to undergo morphogenesis and form biofilm on the catheter fragments in experiments both in vitro and in vivo. Furthermore, it was possible to confirm the pathogenic potential of three of these strains during the disseminated infection test. The identification of several opportunistic yeast species isolated from water and sand samples collected from beaches in Rio de Janeiro and Paraná states, and the presence of virulence factors and the ocurrence of antifungal resistance among them, suggest a potential risk to health of people who use these environments for recreational purposes.